Sensitivity of singular beams in the presence of Zernike aberrations. (August 2015) - Dixit, Awakash; Mishra, Sanjay Kumar; Gupta, Arun Kumar
Abstract: Singular beams in the presence of Zernike aberrations create an opportunity for various applications such as trapping and manipulation of micro-particles, atomic optics and atmospheric optics. In the milieu of importance of the role of aberrations, sensitivity of singular beams with Zernike aberrations is studied. In this paper, the effect of various Zernike aberrations on a singular beam is reported in terms of its Point Spread Function (PSF) deformations. The intensity distributions around the focal plane, i.e. PSF, of the singular beam of various topological charges and in the presence of different strengths of Zernike aberrations are theoretically estimated by the Huygens–Fresnel diffraction integral. Experimentally, the singular beams have been generated and known strengths of Zernike aberration introduced in the beam by a phase-only Spatial Light Modulator. Metric Ensquared Energy is used to analyze the PSF of the corresponding intensity distributions of the singular beams. The experimental results have been validated with numerical simulation. Highlights: The intensity distributions around the focal plane of the singular beams for various orders are numerically estimated. The effect of second and third order Zernike aberrations on the singular beams is theoretically studied. Singular beams have been generated using a phase-only SLM with known strengths of Zernike aberrations. The SLM used in experiment is separately characterized for its inherent aberrations. Sensitiveness of singular beams with aberrations has been simulated and validated using Ensquared Energy.